2017
DOI: 10.1016/j.sleh.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The association between insomnia and prescription opioid use: results from a community sample in Northeast Florida

Abstract: Objective The current analysis examines whether opioid use is associated with insomnia in a community sample, as the consequences of the growing epidemic of prescription opioid use continue to cause public health concern. Study Design A cross-sectional study including 8,433 members in a community outreach program, HealthStreet, in Northeast Florida. Methods Community Health Workers (CHWs) assessed health information, including use of opioids (i.e., Vicodin®, Oxycodone, Codeine, Demerol®, Morphine, Percocet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This may be because prescription sedatives are often prescribed as a treatment for many neurological and psychological conditions including anxiety, insomnia, and muscle relaxation ( Griffin, Kaye, Bueno, & Kaye, 2013 ; Moore, Pariente, & Bégaud, 2015 ); prescription opioids are prescribed to treat both chronic and acute pain ( Beaudoin, Lin, Guan, & Merchant, 2014 ; Boudreau et al, 2009 ). Conditions such as anxiety, insomnia, and muscle relaxation commonly co-occur with pain and that may be one possible reason for using sedatives with opioid analgesics ( Holland et al, 1991 ; Serdarevic, Osborne, Striley, & Cottler, 2017 ). Both opioids and sedatives are central nervous system depressants and the combined use of both drugs can result in significant respiratory depression ( Jann, Kennedy, & Lopez, 2014 ) and increase overdose risk ( Dowell, Haegerich, & Chou, 2016 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because prescription sedatives are often prescribed as a treatment for many neurological and psychological conditions including anxiety, insomnia, and muscle relaxation ( Griffin, Kaye, Bueno, & Kaye, 2013 ; Moore, Pariente, & Bégaud, 2015 ); prescription opioids are prescribed to treat both chronic and acute pain ( Beaudoin, Lin, Guan, & Merchant, 2014 ; Boudreau et al, 2009 ). Conditions such as anxiety, insomnia, and muscle relaxation commonly co-occur with pain and that may be one possible reason for using sedatives with opioid analgesics ( Holland et al, 1991 ; Serdarevic, Osborne, Striley, & Cottler, 2017 ). Both opioids and sedatives are central nervous system depressants and the combined use of both drugs can result in significant respiratory depression ( Jann, Kennedy, & Lopez, 2014 ) and increase overdose risk ( Dowell, Haegerich, & Chou, 2016 ; Sun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combined capacity of the CTSA Program hubs-infrastructure and expertise-is proving to be ideal for deploying and implementing innovative therapies and tools to address the opioid crisis. Thus, the CTSA Program has produced initial work in pain management and opioid research, including community engagement; however, as the response to this crisis continues, efforts must maximize limited resources and develop a synchronized approach that considers existing strengths and expertise [e.g., medication-assisted treatment (MAT), data science, recruitment and retention, EHR technologies, community, pediatrics] while maintaining each hub's local/regional context [20][21][22]. In this context, the CTSA Program facilitates the development of synergistic collaborations to efficiently test and implement meaningful translational research projects to solve specific problems across the translational spectrum.…”
Section: The Ctsa Programmentioning
confidence: 99%
“…Similarly, patients with chronic pain diagnoses receive higher doses of long‐acting opioids on a long‐term basis than those without chronic pain, and rates of opioid dependence have been reported as higher in chronic pain patients as compared to the general population, despite limited efficacy for chronic pain management . Additionally, in a cross‐sectional study of over 8,000 community members, insomnia was 42% more likely among those who reported using prescription opioids compared to those who did not . Sleep quality has also been found to be poorer among opioid‐dependent individuals on methadone maintenance therapy as compared to opioid‐naïve individuals .…”
Section: Discussionmentioning
confidence: 99%
“…32 Additionally, in a cross-sectional study of over 8,000 community members, insomnia was 42% more likely among those who reported using prescription opioids compared to those who did not. 33 Sleep quality has also been found to be poorer among opioid-dependent individuals on methadone maintenance therapy as compared to opioid-na€ ıve individuals. 34 Interestingly, insomnia and short sleep duration have also been found to be significant risk factors for onset of chronic pain, 35,36 with poor sleep increasing anxiety and hyperalgesia to heat, blunt pressure, cold, and pinprick stimuli.…”
Section: Discussionmentioning
confidence: 99%